Case, word order and prominence: interacting cues in language production and comprehension - Lamers, Monique (Studies in theoretical psycholinguistics, 2012)
"Language users have access to several sources of information during the build up of a meaningful construction. These include grammatical rules, situational knowledge, and general world knowledge. A central role in this process is played by the argument structure of verbs, which establishes the syntactic and semantic relationships between arguments. This book provides an overview of recent psycholinguistic and theoretical investigations on the interplay between structural syntactic relations and role semantics. It focuses on the interaction of case marking and word order with semantic prominence features... Taking a broad cross-linguistic perspective, this book offers and interdisciplinary discussion of the interaction of case, word order and prominence with argument structure, and their effects on argument realization and interpretation in language
Keywords: Aufsatzsammlung; Satzsemantik; Argument; Wortstellung; Kasus